Influence of inflammation on bleeding and wound healing following surgical extraction of impacted lower third molars - Yusheng Cheng; Maged Ali Al-Aroomi; Naseem Ali Al-Worafi; Essam Ahmed Al‑Moraissi; Changfu Sun (BMC, 2023)
Abstract Objective This study aimed to investigate the effect of inflammatory states following impacted lower third molar (ILTM) surgery regarding postoperative bleeding and wound healing. Methods The study included patients who underwent extraction of ILTMs associated with or without inflammatory conditions. Post-extraction bleeding and wound healing were assessed. In addition, mean grey values (MGVs) of alveolar bone and bone height using an orthopantomography radiograph were analyzed. Results A total of 376 patients were enrolled; 171 pericoronitis, 51 pulpitis, 44 chronic periapical periodontitis, 36 chronic periodontitis, and 74 control. The bleeding score in the control group was significantly lower than in the periapical periodontitis and periodontitis groups. Excellent wound healing for control, pericoronitis, pulpitis, periapical periodontitis, and periodontitis groups was (78.38%, 35.67%, 70.59%, 70.45%, and 33.33%, respectively). Patients with pericoronitis and periodontitis had significantly poorer wound healing (P < 0.01). The MGV in periapical periodontitis and periodontitis was considerably lower than in the control group. Conclusions The inflammatory conditions associated with ILTMs increase the risk of bleeding. So suturing with the placement of local hemostatic agents over a pressure pack alone is recommended. The poorest wound healing was in localized gingival inflammation. Furthermore, MGV was affected by age and was lower with periapical periodontitis.